Inovasi Pembelajaran Biologi: Integrasi Problem Based Learning Berbantuan Mind Mapping di SMA Negeri 2 Tondano - Sonia Sihombing; Dientje F. Pendong; Ferny M. Tumbel (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Improving students' Biology learning outcomes is a major challenge in the learning process in high school, especially when the material taught is abstract and complex, such as the human digestive system. This study aims to analyze the effectiveness of the Problem-Based learning model assisted by mind mapping in improving the learning outcomes and activities of grade XI students of SMA Negeri 2 Tondano. This research is a Classroom Action Research conducted in two cycles, each consisting of two meetings. Each cycle involves planning, action execution, observation, and reflection activities, with data collection through observation, testing, and documentation. The results of the study showed a significant increase in learning activities and student learning outcomes. The average learning activity increased from 54.6% in the first cycle to 81% in the second cycle, while the percentage of completeness of learning outcomes increased from 59% to 88%. This increase is influenced by the active involvement of students in group discussions, visualisation of concepts through mind mapping, and the role of teachers as facilitators in problem-based learning. These findings indicate that the integration of the Problem-Based model with mind mapping is effective in building critical thinking skills, improving concept understanding, and encouraging active student participation. The implications of this study show the importance of implementing innovative learning strategies to improve the quality of Biology learning in secondary schools.